Sport performance interventions: Evaluating past strategies and providing future recommendations - Denise Hill (International Journal of Sport Psychology, 2020)
The purpose of this review is to highlight the emergence and development of psychological interventions that facilitate optimal performance, and propose future directions for applied sport interventions. Within the past 40 years, educational and alternative psychological skills training strategies (e.g., self-talk, relaxation) have been proposed, and researchers have shown they can be effective in facilitating athletic performance. However, such PST interventions largely promote the removal (or reduction) of unwanted psychological experiences. In contrast, researchers have offered contemporary approaches whereby athletes should be encouraged to increase their capacity to experience unwanted feelings, cognitions, or intentions, rather eliminating them, to increase psychological flexibility for optimal performance. We review this literature and offer future research directions that focus on the use of technology, on-line sport psychology consultancy, and consideration of post-performance assessments, as methods to improve future PST intervention delivery.